Single visit root canal treatment with post crown restoration - Ismiyatin, Kun; Saraswati, Widya; Cahyani, Febriastuti; Vivian Widjaya, Olivia; Ghozali Pangestu, Dede; Arshila, Dea (Conservative Dentistry Journal, 2022)
Background: Single visit endodontics has been shown to be an effective treatment modality when compared with multiple visit therapy and it does not deviate from achieving the objectives of proper biomechanical preparation, debridement, shaping, disinfection and 3 dimensional obturation of root canal system and is more beneficial to the patient and dentist provided there is careful case selection and strict follow of standard endodontic protocols. Symptomatic teeth can also be managed by single visit after controlling the abscess infection with antibiotic, provided the root canal is dry without any discharge.Purpose: This study aims to perform single visit root canals on teeth with irreversible pulpitis and restoration with post core and crown. Case(s): A 48-years-old female comes with dental complaints of upper left rear spontaneous pain at night. The tooth has had cavities since about two years ago and has never been previously treated. The patient said had not any systematic health disorder. There is a spontaneous pain that the patient feels. Case Management: From the examination that has been carried out, a clinical diagnosis of tooth 25 were symptomatic pulpitis irreversible with normal apical tissue. The restoration endodontic treatment plan was a single visit endodontic and the restoration is post core and crown. Conclusion: Symptomatic pulpitis irreversible with normal apical tissue treatment can be carried out single visit root canal treatment. Restoration of post endodontic treatment in this case need fiber post and core using composite and finally restoration using crown that made of zirconia. Zirconia has a higher level of material resistance than lithium disilicate. This is what makes zirconia the choice, especially for posterior teeth.